DIVERSIDAD Y ABUNDANCIA DE AVES EN UN HUMEDAL DEL NORTE DE VERACRUZ, MÉXICO - Serrano, Arturo; Vázquez-Castán, Laura; Ramos-Ramos, Miriam; Basáñez-Muñoz, Agustín de Jesús; Naval-Ávila, Celina (Instituto de Ecología, A.C., 2013)
Mexican coastal and inland wetlands are an important habitat for birds. The loss and degradation of wetlands have been the main threat to birds. Currently, the number of individuals of each bird species found in wetlands is unknown. Thus, the aim of this study was to determine the diversity and abundance of birds in a wetland of northern Veracruz, the Tumilco’s mangrove forest. Distance sampling method and direct observation were used to determine bird diversity and abundance in the mangrove. A total of 63 surveys were done with an effort of 386 effective hours, conducting 274 transects (1 km long) across the study area. A total of 56 birds pecies belonging to 23 families were recorded. There were six species found listed in the NOM-059-SEMARNAT-2010, of which the most abundant species was Anas platyrhynchos diazi and less representative Falco peregrinus. The birds’ abundance estimated for the entire study area was 5945 individuals (coefficient interval at 95% = 5035; CV = 7.25%) and a density of 0.526 birds/ha (coefficient interval at 95% = 0.49; CV = 7.25%). This study shows that the Tumilco mangrove forest is critical for bird conservation in Veracruz.